Diversity order gain for narrow-band multiuser communications with pre-combining group detection. - Fain, E.A (IEEE Transactions on communications)
In narrow-band multiuser communication systems with fading diversity, it is shown that pre-combining group detection can bridge the diversity-order gap in performance between the optimum and linear detectors. For a system with M diversity channels, the group detector diversity order is M-|G|, where |G| is the interfering group size, a design parameter. Group detection thus provides a more substantial improvement in performance in narrow-band channels over linear detection than in wide-band channels in which the diversity orders of the optimal and linear detectors are equal. Here, the complexity of the receiver is a new parameter which, in addition to the number of antennas, can be used to control the diversity order. Exact formulas for the pairwise-error probabilities and bounds for the bit-error rate are obtained, and numerical results are shown